Proteomic responses to nanoparticulate and ionic silver in freshwater microbes with different background - Barros, Diana Cláudia Martins Costa (2018)
ERDF through the COMPETE2020 - Programa Operacional Competitividade e Internacionalização (POCI) and by the Portuguese Foundation for Science and Technology (FCT) I.P. through the strategic funding UID/BIA/04050/2014 (POCI-01-0145-FEDER-007569) and PTDC/AAC-AMB/121650/2010